Media Pengenalan Properti 3D Berbasis Web Aplikasi - Gede Riska Wiradarma; I Nyoman Piarsa; I Ketut Gede Darma Putra (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2017)
Architect is one of business services in creating property design to make it become a reality. To design a property development, an architect requires the ability to visualize the object as a preview design to clients. A mock-up is a way to promote a design property, but as time goes on, the cost in making mock-up is too big and it is usually takes a long time to finish a mock-up, sometimes it burdens the developer. The utilizations of digital medias in this century, are still not enough in promoting an accurately and detailed architectural work, make the information that received by the consumers not optimal, because of it, it is needed appropriate technologies. Computerized technology enables to build the 3D technology on the browser as a promotional tool-based architecture 3D artwork. The WebGL technology gives a lot of advantages to the architect’s side, the construction company’s side and also the property developer’s side. The WebGL technology also makes the architectural work looks real, like 3D programs that are in market. The cloud-based technology can be used in many cases, such as property business.